Ukrainian woman in war: the problem of patriotism and betrayal (based on the material of O. Dovzhenko's literary works) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article declares that Oleksandr Dovzhenko’s literary heritage is a kind of encyclopaedia of the Ukrainian women’s life during the Second World War and post-war years. The writer with the documentary authenticity described all the horrors of life the Ukrainian woman had to pass through at that time. Special attention is given to the problems of the Ukrainian women patriotism and collaboration in the period of occupation.
Keywords: collaboration; patriotism; war; wife; widow; period of occupation; morality